2011
DOI: 10.1093/ageing/afr114
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rates of fragility hip fracture in middle-aged and elderly men and women in southern Norway

Abstract: Age-adjusted incidence of hip fracture in men and women in southern Norway is the lowest reported from Norway and among the lowest in Scandinavia. No differences were seen between rural and urban areas. The number of fragility hip fractures was statistically significant higher in winter compared with the other seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 26 publications
4
30
0
3
Order By: Relevance
“…As previously reported in our incidence study,14 of hip fracture, a total of 951 patients (271 males and 680 females) were identified with a hip fracture in the catchment area in the 2-year period 14. Nine hip fracture patients (four males and five females) could not be identified by the Norwegian National Register, which performed the matching of patients with controls.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As previously reported in our incidence study,14 of hip fracture, a total of 951 patients (271 males and 680 females) were identified with a hip fracture in the catchment area in the 2-year period 14. Nine hip fracture patients (four males and five females) could not be identified by the Norwegian National Register, which performed the matching of patients with controls.…”
Section: Resultsmentioning
confidence: 96%
“…The four hospitals are the only referral centers for orthopedic trauma in southern Norway. Data on incidence of hip fracture from this patient cohort have previously been described in detail 14. In short, the hospital electronic diagnosis registers were used to identify all hip fracture patients coded as S72.0-2 according to the International Classification of Diseases 10th Revision (ICD-10) in the 2-year period 15.…”
Section: Methodsmentioning
confidence: 99%
“…Osteoporosis is widely recognized as an important public health problem because its complications, including fractures, are associated with significant morbidity and mortality (Diamantopoulos, et al, 2012;Magaziner et al, 1989). Peak bone mass is a major risk factor for osteoporotic fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Az incidencia emelkedését az elöregedő társadal-makban a magasabb átlagéletkorral együtt járó mozgás-korlátozottság okozta folyamatos csontállományvesztés is okozza, amellett, hogy az immobilizáció miatti izomműködés romlása a csontállomány további lebomlásával jár, mert az egyre csökkenő fi zikai aktivitás egyre alacsonyabb csonttömeget eredményez. A szezonális viszonyok és egyes társuló krónikus megbetegedések ugyancsak fontos tényezőként tarthatók számon úgy a csípőtáji törések létrejöttében, mind a D-vitamin-hiány-nyal összefüggésbe hozható gyakori időskori betegségek kialakulásában [8,9,10,11,12,13].…”
Section: (Oh)d = 25-hidroxi-d-vitaminunclassified
“…Lips [10] adatai szerint a csípőtörések száma szezonális ingadozást mutat a napsütéses órák számával. Más adatok szerint is a csont denzitásának csökkenésével összehozható törési rizikó változása függ a szezonális viszonyoktól [11]. Egy korábbi adat szerint 1951-1972 között az atmoszféra ózontartalma és a szennyeződés megnövekedése miatt mintegy 20%-kal csökkent a napsugárzás mértéke, s ez együtt járt a csípőtáji törések szaporodásával [12].…”
Section: öSszefüggés a Betegek Műtétet Követő Korai áLlapota éS A D-vunclassified